Moderation of Thought in the Age of Radicalism: The Role of Social Media and Political Education in Countering Hate Content - Abdullah, Munawiah; Amiruddin, M. Hasbi; Dewi, Ernita; Mannan, Nuraini H. A. (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study analyzes the role of social media and political education in moderating thought in the era of radicalism, particularly in dealing with hate content. Social media plays a dual role: disseminating useful information and spreading hate content that incites radicalism. This article uses a qualitative approach with descriptive analysis methods. The research location is in the Province of Aceh. Primary data consists of in-depth interviews with local intellectuals, including academics, religious scholars, and community leaders. The results show that social media significantly influences public opinion and people's mindsets. However, through proper political education, social media can be used to spread values of moderation and tolerance and reduce the impact of hate content. Political education that is inclusive and based on national and humanitarian values has proven effective in instilling a moderate attitude. A curriculum emphasizing dialogue, tolerance, and respect for differences is crucial.